Drag Reduction Using Biomimetic Sharkskin Denticles - Bhatia, D.; Zhao, Y.; Yadav, D.; Wang, J. (Engineering, Technology & Applied Science Research, 2021)
This paper explores the use of sharkskin in improving the aerodynamic performance of aerofoils. A biomimetic analysis of the sharkskin denticles was conducted and the denticles were incorporated on the surface of a 2-Dimensional (2D) NACA0012 aerofoil. The aerodynamic performance including the drag reduction rate, lift enhancement rate, and Lift to Drag (L/D) enhancement rate for sharkskin denticles were calculated at different locations along the chord line of the aerofoil and at different Angles of Attack (AOAs) through Computational Fluid Dynamics (CFD). Two different denticle orientations were tested. Conditional results indicate that the denticle reduces drag by 4.3% and attains an L/D enhancement ratio of 3.6%.